2009
DOI: 10.1200/jco.2008.18.3061
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Testing Approach As an Efficient and Easier Alternative for the Validation of New Predictive Technologies in the Clinic

Abstract: In-clinic validation of predictive technologies will help the clinician adopt truly beneficial technologies and avoid the adoption of technologies which provide no significant benefit to their local patient population. For this task, sequential methods offer clear advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In our study, the highest biopsy Gleason score in ≥8-core biopsies provided a significant independent predictor comparable to serum cysteine and homocysteine. However, routine ultrasound directed first biopsies are reported to miss nearly a quarter of the prostate cancers [19] and often underestimate tumor grade [20], [21]. The combination of serum PSA with cystathionine, cysteine, and homocysteine as markers could improve decision-making for primary treatment and earlier subsequent adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the highest biopsy Gleason score in ≥8-core biopsies provided a significant independent predictor comparable to serum cysteine and homocysteine. However, routine ultrasound directed first biopsies are reported to miss nearly a quarter of the prostate cancers [19] and often underestimate tumor grade [20], [21]. The combination of serum PSA with cystathionine, cysteine, and homocysteine as markers could improve decision-making for primary treatment and earlier subsequent adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This sequential updating process continues until the line crosses either of two decision boundaries. These boundaries are set by Beam et al using statistical theory to limit the probability of a type I error to be no more than 5% and type II error to be no more than 20% [1] In patients with brain metastases, the four-tiered score developed by Rades et al [6] has been shown to predict survival. The score is based on performance status, age, presence of extracranial metastases and interval from first cancer diagnosis to treatment for brain metastases.…”
Section: Resultsmentioning
confidence: 99%
“…The effort to provide a tool for local validation of new prognostic and predictive models is thus timely and helpful. In the present article, we have demonstrated how the validation approach published by Beam et al [1] can be applied to patients receiving palliative radiotherapy outside of clinical trials. We have focused on prediction of poor prognosis (survival < 6 months) by strictly following the methods proposed by Beam et al, including their PPV of 80% and boundaries set to limit the probability of type I error (error in hypothesis testing when the null hypothesis is rejected when it is true) and type II error (error in hypothesis testing when the null hypothesis is not rejected when it is false).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting alternative involves sequential analysis of a series of patients. This may reduce the number needed to validate the model while simultaneously making it more specific for a particular clinic's population 36…”
Section: Predictive Models In Prostate Cancer Detectionmentioning
confidence: 99%